STORYTELLING INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN MENULIS NARASI PADA SISWA KELAS III MI MIFTAKHUL AMAL BLULUK - Nandini, Diajeng Putri; Anwar, Moh. Farid Nurul; Rozhana, Kardiana Metha (Universitas Tribhuwana Tunggadewi, 2025)
This research aims to improve the narrative writing ability and idea expression of third-grade students at MI Miftakhul Amal Bluluk through the application of interactive storytelling, with an emphasis on addressing vocabulary limitations, text structure, and low student motivation. Methods: The study employed Classroom Action Research (CAR) in two cycles with procedures of planning, action, observation, and reflection. Data were collected through narrative writing tests, direct observations, and documentation of students’ work. Analysis data: The data were analyzed descriptively and quantitatively by comparing the mean scores and mastery percentages before and after the action. Result and discussions: The initial average student score was 68.08 with a mastery level of 30%. After the intervention in Cycle I, the score increased to 78.12 with 61.54% mastery, and in Cycle II it reached 81.27 with 88.46% mastery. This improvement was triggered by more varied storytelling techniques, intensive guidance, and written feedback on students’ writing tests. The findings indicate that interactive storytelling improved narrative structure, story flow, and students’ ability to express ideas in writing. Conclusion: Interactive storytelling is an effective instructional approach to developing narrative writing skills in elementary students. Teachers are advised to continuously develop creative storytelling variations and conduct ongoing reflection to create a more immersive, enjoyable, and meaningful writing environment.